Complex Care Curriculum: Pediatric Spasticity - Kavita Parikh; Olga Morozova; Neha Shah; Melanie Anspacher (Association of American Medical Colleges, 2012)
Abstract Children with special health care needs are increasingly prevalent in US hospitals. The pediatric hospitalist is often the primary provider of inpatient care for these patients. However, exposure to this patient population during training varies from provider to provider. No published educational curricula are specific to the inpatient care of this population. The purpose of this project is to provide a multimodal educational curriculum for health care providers with the overall goal of improving inpatient care for this at-risk population. This curriculum is primarily composed of a series of topic-specific learning modules. Asynchronous learning modules, utilized appropriately, can augment learning by providing individualized instruction and mastery of fundamentals. This particular resource was created to provide pediatricians with educational materials related to the care of the medically complex child with spasticity. So far, 17 colleagues have participated in this learning module, with favorable results. On a 5-point Likert scale evaluation, over 90% of respondents felt that this learning module was relevant to clinical practice, changed their clinical practice, and increased their comfort with teaching this topic to trainees. The average pretest score was 64%, and the average posttest score was 82%, which was statistically significant (p < .05).